Use the Chinese herbal compound regulatory network to verify the relationship between the Jun, Chen, Zuo, and Shi of Xiaochaihu Decoction in treating hepatitis - Yuexing Ma; Xiaoqi Meng; Rongbin Pan; Zhixin Zhu; Zirong Peng; Simin Liu; Haoyi Zheng (Elsevier, 2022)
Purpose: To verify the relationship between the monarch(Jun), minister(Chen), assistant(Zuo), and guide(Shi) of Xiaochaihu Decoction in treating hepatitis through the regulation network of traditional Chinese Pharmacy compound. Methods: First, We use the data in the TCMSP database to obtain the effective ingredients and targets of Xiaochaihu Decoction, and screen the effective ingredients. Then, the genes related to hepatitis diseases obtain from the five databases, and the intersection genes with the target genes Xiaochaihu Decoction were screened. Third, We draw the ''traditional Chinese Pharmacy - compound - target (gene)'' network diagram of Xiaochaihu Decoction and hepatitis, then we get the network core of the network. Fourth, We perform GO enrichment analysis and KEGG enrichment analysis on the intersection genes. Fifth, We use molecular docking technology to verify the interaction between crucial targets and compounds. Finally, get data from the Oncomine database for Meta-analysis. We have verified the gene expression and protein expression determination of AKT, IKKs, IκBα through PCR and WB experiments. Results: We screened and obtained the drug target information of Xiaochaihu Decoction, and we finally obtained a total of 163 active ingredients and 6854 hepatitis-related genes. There are 193 genes common to drug targets and hepatitis. We obtained 18 core genes from the Chinese herbal compound regulatory network diagram. The results of Meta-analysis and molecular docking are both ideal. It proved that Xiaochaihu Decoction has an inhibitory effect on the TNF signaling pathway and the gene expression of AKT, IKKs, and IκBα. The Jun (Monarch) Chen (Minister) medicine plays an essential guiding role in Xiaochaihu Decoction. Conclusions: The results obtained through the Chinese herbal compound regulatory network analysis can scientifically explain the relationship between the Jun (Monarch), Chen (Minister), Zuo (Assistant), and Shi (Guide) of Xiaochaihu Decoction.